Quantifying the contributions of climate factors and human activities to variations of net primary productivity in China from 2000 to 2020 - Li, Zijian; Chen, Jiangping; Chen, Zhanpeng; Sha, Zongyao; Yin, Jianhua; Chen, Zhaotong (Frontiers in Earth Science, 2023)
Net primary productivity (NPP) plays a vital role in the globe carbon cycle. Quantitative assessment of the effects of climate changes and human activities on NPP dynamics is vital for understanding the driving mechanisms of vegetation change and sustainable development of ecosystems. This study investigates the contributions of climatic factors and human activities to vegetation productivity changes in China from 2000 to 2020 based on the residual trend analysis (RESTREND) method. The results showed that the annual average NPP in China was 325.11 g C/m2 from 2000 to 2020 and NPP showed a significantly increasing trend at a rate of 2.32 g C/m2/year. NPP increased across 64.54% of China over the study period, while only 9.90% showed a declining trend. The contributions of climatic factors and human activities to NPP increase were 1.169 g C/m2/year and 1.142 g C/m2/year, respectively. Climate factors contributed positively mainly in Sichuan Basin, the Loess Plateau, the Mongolian Plateau, and Northeast China Plain. Positive contributions of human activities to NPP mainly occurred in the Loess Plateau, Central China, and the Greater Khingan Mountains. The effects of climatic factors and human activities on NPP changes varied among sub-regions. In Tropical Monsoon Climate Region and Subtropical Monsoon Climate Region, human activities had greater impacts on NPP increase than climate factors, while climate factors were the dominant factor for NPP recovery in other sub-regions. In addition, during 2000 to 2020, NPP was dominated by both climate factors and human activities in 49.84% of China, while areas dominated solely by climate factors and human activities accounted for 13.67% and 10.92%, respectively. Compared to changed land cover types, the total NPP as well as the increase of total NPP in China was mostly contributed by unchanged land cover types, which contributed more than 90%.